2023
DOI: 10.1111/acel.14046
|View full text |Cite
|
Sign up to set email alerts
|

Abalone peptide increases stress resilience and cost‐free longevity via SKN‐1‐governed transcriptional metabolic reprogramming in C. elegans

Qiangqiang Wang,
Liangyi Wang,
Ziliang Huang
et al.

Abstract: A major goal of healthy aging is to prevent declining resilience and increasing frailty, which are associated with many chronic diseases and deterioration of stress response. Here, we propose a loss‐or‐gain survival model, represented by the ratio of cumulative stress span to life span, to quantify stress resilience at organismal level. As a proof of concept, this is demonstrated by reduced survival resilience in Caenorhabditis elegans exposed to exogenous oxidative stress induced by paraquat or with endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…As previously, we used paraquat, a potent ROS generator, at a high dose (50 mM) to cause a lethal oxidative stress for rapid survival assay and at a low dose (2 mM) to generate a mild, nonlethal oxidative stress for ROS determination. 10,13 As shown in Fig. 3C, the survival rate of the wild-type nematodes pretreated with the UF<3K peptides was considerably increased when exposed to 50 mM paraquat as compared to the control nematodes exposed to paraquat alone, particularly for the 2.0 and 4.0 mg mL −1 peptide treat-…”
Section: Inhibition Of Neuronal Degeneration By Sea Cucumber Peptide ...mentioning
confidence: 82%
See 4 more Smart Citations
“…As previously, we used paraquat, a potent ROS generator, at a high dose (50 mM) to cause a lethal oxidative stress for rapid survival assay and at a low dose (2 mM) to generate a mild, nonlethal oxidative stress for ROS determination. 10,13 As shown in Fig. 3C, the survival rate of the wild-type nematodes pretreated with the UF<3K peptides was considerably increased when exposed to 50 mM paraquat as compared to the control nematodes exposed to paraquat alone, particularly for the 2.0 and 4.0 mg mL −1 peptide treat-…”
Section: Inhibition Of Neuronal Degeneration By Sea Cucumber Peptide ...mentioning
confidence: 82%
“…Since behavioral dysfunction is a major symptom of many neurodegenerative diseases, we then examined the effect of the peptide on locomotion-related behavior as previously. 10,47 We found that both crawling speed and body bends of the polyQ nematodes were improved on Day 7 of adulthood after the peptide treatment (Fig. 5C).…”
Section: Papermentioning
confidence: 84%
See 3 more Smart Citations